2004
DOI: 10.1002/xrs.715
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting tunnel junctions as detectors for high‐resolution x‐ray spectroscopy

Abstract: Superconducting tunnel junctions (STJs) are a type of cryogenic detector with a working temperature of about 100 mK. They allow the combination of low energy threshold, high quantum efficiency and good count rate capability with an excellent energy resolution; at an x-ray energy of 5.9 keV an energy resolution of 10.8 eV (FWHM) has been achieved. The detector system described is based on STJs which consist of two superconducting Al electrodes separated by a thin dielectric tunnel barrier. The tunneling process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Going to lower T c , and hence lower operating temperature, improves the theoretical R. Operating at 100 mK yields a theoretical spectral resolution of R ≈ 100 at 400 nm. Previous research with superconducting tunnel junctions (STJs) with superconducting absorbers has shown that superconducting absorbers can approach the Fano limit (Li et al 2001;Huber et al 2004;le Grand et al 1998).…”
Section: Microwave Kinetic Inductance Detectorsmentioning
confidence: 99%
“…Going to lower T c , and hence lower operating temperature, improves the theoretical R. Operating at 100 mK yields a theoretical spectral resolution of R ≈ 100 at 400 nm. Previous research with superconducting tunnel junctions (STJs) with superconducting absorbers has shown that superconducting absorbers can approach the Fano limit (Li et al 2001;Huber et al 2004;le Grand et al 1998).…”
Section: Microwave Kinetic Inductance Detectorsmentioning
confidence: 99%
“…The review year has seen a welcome recovery in the number of publications on ultra-high energy resolution cryogenic detectors. Huber and colleagues 18 described a new superconducting tunnel junction (STJ) comprising two aluminium electrodes and a novel isolated lead (Pb) absorber, which improved absorption efficiency at 6 keV from o1% to around 50% and significantly reduced detector artefacts. A thin (1.3 mm) layer of silicon monoxide was used to protect the lead absorber from oxidation, and although this additional layer slightly degraded the energy resolution, it eliminated serious perfor-mance degradation previously observed with lead alone.…”
Section: Detectorsmentioning
confidence: 99%